If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(1 + -1y) + -3(y + 2) = 2(y + 1) (1 * 8 + -1y * 8) + -3(y + 2) = 2(y + 1) (8 + -8y) + -3(y + 2) = 2(y + 1) Reorder the terms: 8 + -8y + -3(2 + y) = 2(y + 1) 8 + -8y + (2 * -3 + y * -3) = 2(y + 1) 8 + -8y + (-6 + -3y) = 2(y + 1) Reorder the terms: 8 + -6 + -8y + -3y = 2(y + 1) Combine like terms: 8 + -6 = 2 2 + -8y + -3y = 2(y + 1) Combine like terms: -8y + -3y = -11y 2 + -11y = 2(y + 1) Reorder the terms: 2 + -11y = 2(1 + y) 2 + -11y = (1 * 2 + y * 2) 2 + -11y = (2 + 2y) Add '-2' to each side of the equation. 2 + -2 + -11y = 2 + -2 + 2y Combine like terms: 2 + -2 = 0 0 + -11y = 2 + -2 + 2y -11y = 2 + -2 + 2y Combine like terms: 2 + -2 = 0 -11y = 0 + 2y -11y = 2y Solving -11y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -11y + -2y = 2y + -2y Combine like terms: -11y + -2y = -13y -13y = 2y + -2y Combine like terms: 2y + -2y = 0 -13y = 0 Divide each side by '-13'. y = 0 Simplifying y = 0
| 3x-6y+10=0 | | 7x-9-11-x=12 | | 8(1-x)-3(2-2x)=2(x+1) | | 5y+27+4y=9 | | 57-5x=4x+23 | | 4x(x-7)+13=27 | | 8-7x=31-4x | | 8.7=d+8.7 | | 5x-(2x+3)=4x-30 | | 4(7x+7)-5=28x+23 | | y=11x^2-90x-68 | | 15x+6y=0 | | (16+2x)*(16+2x)=228 | | 4x-8=4(x+4) | | 4(w+2x)+9w= | | 1.5=r+4.5 | | 1.5=r | | 2x-2y=11 | | 9(3x-5)=(5x+3)+7 | | 5x+1=8x+6 | | -18=162 | | -4(3a+2)=52 | | 48400=(2x+2)(x) | | y=25x^2+10x-24 | | 8.4+b=-22.9 | | -3(x-4)+7x=8x+-8 | | 12+2l+2w=12 | | 4(2a+1)=60 | | 3X+2Y=34 | | 61=4+q | | 7x^2+28x+196=0 | | -5(t-1)+t=5t-9 |